Antioxidant and Protective Effects of Artemisia campestris Essential Oil Against Chlorpyrifos-Induced Kidney and Liver Injuries in Rats - Saoudi, Mongi; Badraoui, Riadh; Rahmouni, Fatma; Jamoussi, Kamel; El Feki, Abdelfattah (Frontiers in Physiology, 2021)
This study is aimed to elucidate the possible antioxidant and protective effects of Artemisia campestris essential oil (ACEO) against the deleterious effects of chlorpyrifos (CPF) in rats. The in vivo study revealed increases in aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) activities and the serum contents of creatinine, urea, uric acid, cholesterol, triglycerides, low density lipoproteins (LDL) and glucose in rats treated with CPF as compared to controls. Meanwhile, hepatic and renal activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) in liver and kidney decreased and the content of malondialdehyde (MDA) increased. Some histopathologic features were noticed in liver and kidney of the CPF group. Interestingly, ACEO alleviated the biochemical disruptions and reduced these hepato-renal morphologic changes.